A prospective comparative study on the use of nanocrystalline silver ion dressing with normal saline dressing in diabetic foot ulcers - Malligurki, Vamsi K.; Fatima, Samar; Anmol, Ruhee; Thimmegowda, Prashanth Annayyanapalya (International Surgery Journal, 2021)
Background: A diabetic foot is any pathology that results directly from peripheral arterial disease and/or sensory neuropathy affecting the feet in diabetes mellitus. Proper assessment of the wound followed by an aggressive multidisciplinary approach can reduce the risk of amputation, thereby greatly increasing the patient’s quality of life. Wound dressings play a vital role in diabetic foot care management. Nanocrystalline silver ion dressing is a newer modality that has been in consideration for the treatment of diabetic wounds. Methods: This was a prospective comparative study conducted in the department of general surgery, Sagar hospital-DSI, Bangalore from December 2020 to March 2021. A total of 50 diabetic patients were included in the study and were randomised into the study group and control group. The study group received nanocrystalline silver ion dressings while the control group received dressings with normal saline. Patients were observed for 8 weeks. Data regarding the presence of wound discharge, type of discharge, granulation tissue, presence of slough and changes in the size of the wound was recorded and analysed. Results: Study group showed statistically significant better outcomes (p<0.05) in terms of reduced wound discharge, early granulation tissue, rapid reduction of slough from wounds and reduction in the wound size when compared with the control group. 17 patients responded completely in the study group when compared with the control group, where 8 patients have got a complete response (p<0.05). Conclusions: Wound dressings with nanocrystalline silver ion helps in the early healing of diabetic foot ulcers when compared to normal saline dressings.